Finite element model for crack propagation using master-workers method - Ahmad Kamal Ariffin,; Choy , Hau Yan; Mohd Jailani Mohd Nor, (2004)
This paper describes an algorithm for parallel assembling of the stiffness matrix in simulation of crack propagation in distributed memory environment using masterworkers method. In this algorithm, element stiffness matrix is formed by groups in each processor related by the finite element mesh. Each processor assembles a specific group of elements and no synchronization is required to avoid two or more worker processors sending the calculation result to master processor concurrently. This paper gives the speed-up rate in the simulation of crack propagation. The results indicate excellent performance and reduction of total computational time